Non-financial Indicators of Fraudulent Bankruptcy - M. A. Gorodilov; A. S. Belyaev (Учёт. Анализ. Аудит, 2019)
The article considers what indicators in addition to the existing methods could be used as indication of deliberate bankruptcy. The analysis of the patterns identified during forensic accounting examinations in order to find the signs of fraudulent bankruptcies shows that there should exist non-financial indicators of a company’s preparation to fraudulent bankruptcy. The authors analyze the economic activity of seven organizations in the period preceding their filing for bankruptcy. These data were systemized and subjected to further examination. The analysis resulted in determining two non-financial indicators of the fraudulent nature of bankruptcy. The indicators identified can be used by court receivers when they analyze financial and economic activities of the companies, as well as by forensic accountants in cases of bankruptcy.